Reformacija v zgodovinskem romanu Ilke Vašte Gričarji - Borovnik, Silvija (Slavia Centralis, 2020)
The Reformation in the Historical Novel Gričarji by Ilka Vašte The article deals with the subject of Reformation in the historical novel Gričarji published in 1956 by Ilka Vašte. Vašte was one of the most prolific female Slovenian novelists. During the period of social realism and later during the modernist movements in Slovene prose, she was underrated. The article explores the reasons her work was neglected. The historical novel Gričarji, dealing with the Slovenian Reformation and Counter-Reformation in Dolenjska and the wider region, provides an interesting answer.